Minority carrier lifetime in indium doped silicon for photovoltaics. (6th August 2019) - Murphy, John D.; Pointon, Alex I.; Grant, Nicholas E.; Shah, Vishal A.; Myronov, Maksym; Voronkov, Vladimir V.; Falster, Robert J.
Abstract: For photovoltaics, switching the p ‐type dopant in silicon wafers from boron to indium may be advantageous as boron plays an important role in the light‐induced degradation mechanism. With the continuous Czochralski crystal growth process it is now possible to produce indium doped silicon substrates with the required doping levels for solar cells. This study aims to understand factors controlling the minority carrier lifetime in such substrates with a view to enabling the quantification of the possible benefits of indium doped material. Experiments are performed using temperature‐dependent Hall effect and injection‐dependent carrier lifetime measurements. The recombination rate is found to vary linearly with the concentration of un‐ionized indium which exists in the sample at room temperature due to indium's relatively deep acceptor level at 0.15 eV from the valence band. Lifetime in indium doped silicon is also shown to degrade rapidly under illumination, but to a level substantially higher than in equivalent boron doped silicon samples. A window of opportunity exists in which the minority carrier lifetime in degraded indium doped silicon is higher than the equivalent boron doped silicon, indicating it may be suitable as the base material for front contact photovoltaic cells. Abstract : Producing silicon substrates with indium doping instead of boron could provide a route towards reducing degradation. We determine factors which control the minority carrier lifetime in indium doped silicon. Recombination mainly occurs due to un‐ionized indium with a state 0.15 eV from the valence band edge. Indium doped silicon also experiences lifetime degradation, but the degraded lifetimes are higher than with equivalent boron doped samples, showing a window of opportunity exists for indium doped substrates for photovoltaics.